Barriers to Accessing Healthy Food and Food Assistance During the COVID-19 Pandemic and Racial Justice Uprisings: A Mixed-Methods Investigation of Emerging Adults’ Experiences - Larson, Nicole; Alexander, Tricia; Slaughter-Acey, Jaime C.; Berge, Jerica; Widome, Rachel; Neumark-Sztainer, Dianne (Journal of the Academy of Nutrition and Dietetics, 2021)
A steep rise in food insecurity is among the most pressing US public health problems that has resulted from the COVID-19 pandemic. This study aimed to (1) describe how food-insecure emerging adults are adapting their eating and child-feeding behaviors during COVID-19 and (2) identify barriers and opportunities to improve local food access and access to food assistance. The COVID-19 Eating and Activity Over Time study collected survey data from emerging adults during April to October 2020 and completed interviews with a diverse subset of food-insecure respondents. A total of 720 emerging adults (mean age: 24.7 ± 2.0 years; 62% female; 90% living in Minnesota) completed an online survey, and a predominately female subsample (n = 33) completed an interview by telephone or videoconference. Survey measures included the short-form of the US Household Food Security Survey Module and 2 items to assess food insufficiency. Interviews assessed eating and feeding behaviors along with barriers to healthy food access. Descriptive statistics and a hybrid deductive and inductive content analysis. Nearly one-third of survey respondents had experienced food insecurity in the past year. Interviews with food-insecure participants identified 6 themes with regard to changes in eating and feeding behavior (eg, more processed food, sporadic eating), 5 themes regarding local food access barriers (eg, limited enforcement of COVID-19 safety practices, experiencing discrimination), and 4 themes regarding barriers to accessing food assistance (eg, lack of eligibility, difficulty in locating pantries). Identified recommendations include (1) expanding the distribution of information about food pantries and meal distribution sites, and (2) increasing fresh fruit and vegetable offerings at these sites. Interventions of specific relevance to COVID-19 (eg, stronger implementation of safety practices) and expanded food assistance services are needed to improve the accessibility of healthy food for emerging adults.